If it's not what You are looking for type in the equation solver your own equation and let us solve it.
g(10)=-3(10)+1
We simplify the equation to the form, which is simple to understand
g(10)=-3(10)+1
Reorder the terms in parentheses
+(+10g)=-3*(10)+1
Remove unnecessary parentheses
+10g=-3+*(+10+)+1
Reorder the terms in parentheses
+10g=+(-30)+1
Remove unnecessary parentheses
+10g=-30+1
We move all terms containing g to the left and all other terms to the right.
+10g=-30+1
We simplify left and right side of the equation.
+10g=-29
We divide both sides of the equation by 10 to get g.
g=-2.9
| 5x-4+5=6x+3-5 | | 5x-4+5=6x+3-5 | | 5x-4+5=6x+3-5 | | n^2=72 | | 5x-4+5=6x+3-5 | | 5x-4+5=6x+3-5 | | 5x-4+5=6x+3-5 | | 5x-6y=24fory | | (-9-7)(2-7) | | 5x-4+5=6x+3-5 | | 5x-4+5=6x+3-5 | | 5x-4+5=6x+3-5 | | n^2=72 | | n^2-72 | | 3s-4b-13 | | 30x^2,66x^5 | | g(-2)=-3(-2)+1 | | (3)(2x^2-3x+1)=0 | | n+(45)=19 | | (-4x^3y)(x^7^5) | | 3.7x-4.2=3.2x | | 37+11b= | | n^2=-72 | | -8-7x+12+9x+3 | | 6x+.5x=6.7 | | (3x^7)(-3x^7)= | | 6x+.5x=-6.7 | | 3a-5a-2=6a | | 22=-.57(72)+x | | 2y+3y-7y+4=16-2y | | 3a-5a-2 | | 10+11b= |